2019
DOI: 10.1093/mnras/stz2074
|View full text |Cite
|
Sign up to set email alerts
|

Spin frequency evolution and pulse profile variations of the recently re-activated radio magnetar XTE J1810–197

Abstract: After spending almost a decade in a radio-quiet state, the Anomalous X-ray Pulsar XTE J1810-197 turned back on in early December 2018. We have observed this radio magnetar at 1.5 GHz with ∼daily cadence since the first detection of radio re-activation on 8 December 2018. In this paper, we report on the current timing properties of XTE J1810-197 and find that the magnitude of the spin frequency derivative has increased by a factor of 2.6 over our 48-day data set. We compare our results with the spin-down evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 38 publications
(69 reference statements)
9
64
0
Order By: Relevance
“…The position angle is typically difficult to interpret, especially since it is shown to change with time. This variability of polarised emission was confirmed when XTE J1810−197 recently switched on as a radio source again ten years after the cease of its radio emission in 2008 (Levin et al 2019;Dai et al 2019).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…The position angle is typically difficult to interpret, especially since it is shown to change with time. This variability of polarised emission was confirmed when XTE J1810−197 recently switched on as a radio source again ten years after the cease of its radio emission in 2008 (Levin et al 2019;Dai et al 2019).…”
Section: Introductionmentioning
confidence: 70%
“…Radio-loud magnetars are known to show drastic change in their radio pulse profile within a few weeks from the onset of the X-ray outburst (e.g. Camilo et al 2007a;Levin et al 2019), and this is no different for Swift J1818.0−1607. The initial observations with the Effelsberg and Lovell radio tele- Table 3.…”
Section: Profile Evolution In Time and Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…This observation highlights the importance of obtaining a TPA legacy dataset with long enough sequences of single pulses for the brightest pulsars to quantify the pulse-to-pulse variability. XTE J1810−197: Following an X-ray outburst (Gotthelf et al 2019), this magnetar recently switched back on in the radio and was observed with the Parkes telescope by Dai et al (2019) and with the Lovell and Effelsberg telescopes by Levin et al (2019). Figure 4 shows a single pulse from the magnetar in data taken on 2019 March 15 showing the spiky nature of its emission.…”
Section: Pulsars Of Interest Psr J0045−7319mentioning
confidence: 99%